2022
DOI: 10.2147/jpr.s371022
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio as an Indicator of Opioid-Induced Immunosuppression After Thoracoscopic Surgery: A Randomized Controlled Trial

Abstract: Purpose The neutrophil-to-lymphocyte ratio (NLR) is a useful prognostic marker for various diseases and surgery-induced immunosuppression. While opioids are important in general anesthesia, the association between immediate perioperative immune monitoring and opioid consumption for postoperative analgesia after video-assisted thoracoscopic surgery (VATS) is unknown. We aimed to investigate the effect of analgesic techniques on opioid-induced immune perturbation, and the feasibility of NLR as an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Several studies have shown that opioids inhibit the activity of immune cells [20,21]. Chen et al [22], in a study examining the impact of perioperative opi-oid use on the immune system, administered opioidbased analgesia to one group and thoracic paravertebral block (PVB) to another group in 80 patients undergoing thoracoscopic lobectomy. They compared postoperative NLR values between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that opioids inhibit the activity of immune cells [20,21]. Chen et al [22], in a study examining the impact of perioperative opi-oid use on the immune system, administered opioidbased analgesia to one group and thoracic paravertebral block (PVB) to another group in 80 patients undergoing thoracoscopic lobectomy. They compared postoperative NLR values between the two groups.…”
Section: Discussionmentioning
confidence: 99%